Peliosanthes separata (Asparagaceae), a new species from Laos with rare structure of androecium - Vislobokov, Nikolay A. (Phytotaxa, 2016)
Region of SE Asia is a hot spot of biodiversity for such genera of Asparagaceae as Aspidistra Ker Gawler (1822: 628), Peliosanthes Andrews (1808: 605) and Tupistra Ker Gawler (1814: 1655) (Averyanov & Тanaka 2012, Averyanov et al. 2013, 2015a, 2015b, Vislobokov et al. 2014, 2016, Vislobokov 2015), which were considered earlier within Convallariaceae s.str. (Dahlgren 1989).